Risk-adjusted screening for prostate cancer: defining the low-risk group by data from the PROBASE trial - Krilaviciute, Agne; Kaaks, Rudolf; Seibold, Petra Beate; De Vrieze, Maxime; Lakes, Jale; Radtke, Jan Philipp; Kuczyk, Markus A.; Harke, Nina Natascha; Debus, Jürgen; Fink, Christoph Andreas; Herkommer, Kathleen; Gschwend, Jürgen E.; et al. (European urology, 2024)
Background - Risk-adjusted screening for prostate cancer (PCa) aims to reduce harms by less frequent retesting, especially in men at a low risk of PCa. Definitions of low risk are based mainly on studies in men starting screening at age 55-60 yr. - Objective - To identify men at age 45 yr with a low risk of PCa. - Design, setting, and participants - A population-based, risk-adjusted PCa screening trial was conducted in Germany using baseline prostate-specific antigen (PSA) starting in young men (PROBASE). - Intervention - PSA measurements starting at the age of 45 yr. - Outcome measurements and statistical analysis - The incidence of PCa within 5 yr was assessed in men with screen-negative baseline PSA <1.5 ng/ml compared with those with PSA 1.5-≤3.0 ng/ml. - Results and limitations - Of 23301 men who received a first PSA test at age 45 yr, 0.79% had a screen-positive PSA value of ≥3 ng/ml. Among the 89% of men who had a screen-negative baseline PSA value of <1.5 ng/ml, only 0.45% received a positive PSA test ≥3 ng/ml upon retesting after 5 yr. By contrast, for those with a screen-negative baseline PSA value of 1.5-3 ng/ml, 13% surpassed 3 ng/ml upon biennial testing within the next 4 yr. The incidence of PCa in subsequent screening rounds increased with increasing baseline PSA levels, from 0.13 per 1000 person-years for men with initial PSA level of <1.5 ng/ml to 8.0 per 1000 person-years for those with PSA levels of 1.5-3.0 ng/ml. A limitation is a follow-up time of only 5 yr, so far. - Conclusions - Men with baseline PSA <1.5 ng/ml at age 45 yr are at a very low risk of PCa over the next 5 yr. - Patient summary - The PROBASE study showed that men with baseline prostate-specific antigen (PSA) <1.5 ng/ml at age 45 yr have a very low prostate cancer detection rate over 5 yr and do not need PSA retesting during this time.
Gesehen am 21.01.2026
Online veröffentlicht: 15. Mai 2024